JUDGES' CONSIDERATIONS IN PKPU DECISIONS AGAINST DEBTORS UNDERGOING HOMOLOGATION - Simandalahi, Eli Ristiana; Anggusti, Martono; Nababan, Roida (PT. Altin Riset Publishing, 2025)
This study aims to analyze the legal considerations of judges in PKPU decisions against debtors who are executing homologation decisions and examine the legal provisions related to PKPU applications against the same debtor based on Law No. 37 of 2004. This study also highlights the legal phenomena related to two different decisions (homologation and bankruptcy) that occur to the same debtor and their legal impact on the company. The method used in this research is a normative juridical approach with a case study of PT Sabang Subur. Data was collected through literature study and analysis of related court decisions. The results showed that the differences in legal interpretation in the application of PKPU to debtors who have carried out homologation can lead to legal uncertainty. Therefore, this research is expected to provide insight for legal practitioners regarding the aspects that need to be considered in making legal decisions related to PKPU applications to create legal certainty and justice in Indonesia.